An Empirical Study on Organizational Determinants of RFID Adoption in the Logistics Industry - Lin,Chieh-Yu (Universidad Alberto Hurtado. Facultad de Economía y Negocios, 2009)
Radio frequency identification technology (RFID) has been taken as an important application in logistics operations. However, scarce attention has been paid on empirically studying factors affecting the adoption of RFID in the logistics industry. The main purpose of this paper is to study organizational determinants of RFID adoption by logistics companies. A questionnaire survey on logistics companies in Taiwan was conducted to test proposed research hypotheses. Research findings reveal that organizational support for innovation, the quality of human capital, organizational knowledge accumulation, and company size are significantly positively associated with the adoption of RFID. According to research results, managerial implications and opportunities for future research are discussed as well.